Pelatihan Penggunaan Alat Ukur di SMK Ash Shiddiqiyah Balingasal Padureso - Jati Sumarah; Ajeng Tiara Wulandari; Asni Tafrikhatin (JURPIKAT (Jurnal Pengabdian Kepada Masyarakat), 2023)
The skill of measuring an object for a student is an ability that must be possessed, especially for students at the Ash Shiddiqiyah Balingasal Padureso Vocational High School (SMK) Light Vehicle and Automotive Engineering Study Program (TKRO). Automotive skills subjects place great emphasis on the use of measuring tools, including vernier calipers and screw micrometers. The aim of the service is to provide information about the use of vernier calipers and screw micrometers. The implementation of the service uses methods in the form of training on measuring tools with vernier calipers and screw micrometers which is carried out at Ash Shiddiqiyah Balingasal Padureso Vocational School. It is hoped that by providing training on vernier caliper and screw micrometer measuring instruments, students will become proficient in using or operating measuring instruments and can overcome the problem of uncertainty in measurements and understand automotive subjects more easily